Bronchial needle aspiration in the diagnosis of bronchial carcinoma. Issue 7 (July 1981) - Buirski, G; Calverley, P M; Douglas, N J; Lamb, D; McIntyre, M; Sudlow, M F; White, H
Abstract : Sixty consecutive patients with central bronchial carcinomas were studied by fibreoptic bronchoscopy. In all forceps biopsy and bronchial needle aspiration were performed, and in 54 bronchial brushings were obtained. The combination of bronchial brushings and forceps biopsy diagnosed bronchial carcinoma of a defined cell type in 80% of patients. Bronchial needle aspiration was the most effective single technique giving a cytological diagnosis in 80% of patients, and when all three techniques were combined the positive rate increased to 92%. No major complications occurred using bronchial needle aspiration. Needle aspiration was particularly helpful when sampling from lesions in the upper lobes where forceps biopsies were technically difficult, from tumours lying submucosally, and from abnormalities caused by extrinsic compression. We conclude that bronchial needle aspiration should be used routinely, together with other sampling techniques, in the diagnosis of central bronchial carcinoma with the fibreoptic bronchoscope.